Clickable Poly(ethylene glycol)‐Microsphere‐Based Cell Scaffolds. Issue 8 (4th March 2013) - Nguyen, Peter K.; Snyder, Christopher G.; Shields, Jason D.; Smith, Amanda W.; Elbert, Donald L.
Abstract Clickable poly(ethylene glycol) (PEG) derivatives are used with two sequential aqueous two‐phase systems to produce microsphere‐based scaffolds for cell encapsulation. In the first step, sodium sulfate causes phase separation of the clickable PEG precursors and is followed by rapid geleation to form microspheres in the absence of organic solvent or surfactant. The microspheres are washed and then deswollen in dextran solutions in the presence of cells, producing tightly packed scaffolds that can be easily handled while also maintaining porosity. Endothelial cells included during microsphere scaffold formation show high viability. The clickable PEG‐microsphere‐based cell scaffolds open up new avenues for manipulating scaffold architecture as compared with simple bulk hydrogels.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>